Harnessing Artificial Intelligence for Development on the Post-COVID-19 Era : A Review of National AI Strategies and Policies - World Bank (World Bank, Washington, DC, 2021)
Artificial intelligence (AI) has rapidly emerged as an important topic for the global development agenda, and the Coronavirus (Covid-19) pandemic is also yielding new and innovative AI applications and solutions. However, the development of AI technologies remains heavily concentrated in a small number of advanced economies which have access to a strong local talent pool, a robust research and development base and access to capital to fuel growth through investment. Many countries that have seen broad development and adoption also have a national strategic direction for AI defined by their governments. This working paper explores some of these approaches to AI across 11 countries at different stages of digital maturity and economic development, mapping initiatives to different policy domain areas and identifying the tools and instruments that have been proposed to implement AI strategies.